Prisoners’ access to HIV services in southern Malawi: a cross-sectional mixed methods study - Gondwe, Austrida (BMC Public Health, 2021)
BACKGROUND: The prevalence of Human Immunodeficiency Virus (HIV) among prisoners remains high in many countries, especially in Africa, despite a global decrease in HIV incidence. Programs to reach incarcerated populations with HIV services have been implemented in Malawi, but the success of these initiatives is uncertain. We explored which challenges prisoners face in receiving essential HIV services and whether HIV risk behavior is prevalent in prisons. METHODS: We conducted a mixed-methods (qualitative and quantitative), cross-sectional study in 2018 in six prisons in Southern Malawi, two large central prisons with on-site, non-governmental organization (NGO) supported clinics and 4 smaller rural prisons. Four hundred twelve prisoners were randomly selected and completed a structured questionnaire. We conducted in-depth interviews with 39 prisoners living with HIV, which we recorded, transcribed and translated. We used descriptive statistics and logistic regression to analyze quantitative data and content analysis for qualitative data. RESULTS: The majority of prisoners (93.2%) were male, 61.4% were married and 63.1% were incarcerated for 1–5 years. Comprehensive services were reported to be available in the two large, urban prisons. Female prisoners reported having less access to general medical services than males. HIV risk behavior was reported infrequently and was associated with incarceration in urban prisons (adjusted odds ratio [aOR] 18.43; 95% confidence interval [95%-CI] 7.59–44.74; p = < 0.001) and not being married (aOR 17.71; 95%-CI 6.95–45.13; p = < 0.001). In-depth interviews revealed that prisoners living with HIV experienced delays in referrals for more severe illnesses. Prisoners emphasized the detrimental impact of poor living conditions on their personal health and their ability to adhere to antiretroviral therapy (ART). CONCLUSIONS: Malawian prisoners reported adequate knowledge about HIV services albeit with gaps in specific areas. Prisoners from smaller, rural prisons had suboptimal access to comprehensive HIV services and female prisoners reported having less access to health care than males. Prisoners have great concern about their poor living conditions affecting general health and adherence to ART. These findings provide guidance for improvement of HIV services and general health care in Malawian institutionalized populations such as prisoners.